The Effect of Stress Inoculation Group Training on Hope and Quality of Life in Women with Breast Cancer - Alireza Mohammadi Arya; Mahdiyeh Pakdaman; Shahnam Abolghasemi; Mansour Rezaee; Tahereh Pashaee; Amaneh Ghareh Tapeh (Golestan University of Medical Sciences, 2014)
Background and Objective: Breast cancer is the most common cancer among women worldwide. Thus, we aimed to determine the effect of stress inoculation group training on the hope and quality of life in women with breast cancer. Material and Methods: This experimental study was conducted on 60 randomly selected women in chemotherapy ward of Razi hospital in Rasht, 2011. The instruments were Schneider hope and quality of life (SF-36) questionnaires. Of 60, 30 eligible patients were randomly divided into control group with no training and experimental group with stress inoculation training. Results: Before intervention, the two groups were matched with demographic variables, hope and quality of life score. The results showed that the stress inoculation group training is effective both on hope and quality of life. Furthermore, the effect of this approach on quality of life was more than hope score (P=0.001). Conclusion: Stress inoculation group training is highly effective in improving the hope and quality of life in women with breast cancer. To be sure about its permanent effect, further research with follow-up period is needed.